Dioxin and Related Compound Detection: Perspectives for Optical Monitoring - Patrizi, Barbara (Int J Mol Sci, 2019)
Dioxins and related compounds are environmental xenobiotics that are dangerous to human life, due to the accumulation and persistence in the environment and in the food chain. Cancer, reproductive and developmental issues, and damage to the immune system and endocrine system are only a few examples of the impact of such substances in everyday life. For these reasons, it is fundamental to detect and monitor these molecules in biological samples. The consolidated technique for analytical evaluation is gas chromatography combined with high-resolution mass spectrometry. Nowadays, the development of mid-infrared optical components like broadband laser sources, optical frequency combs, high performance Fourier-transform infrared spectroscopy, and plasmonic sensors open the way to new techniques for detection and real time monitoring of these organic pollutants in gaseous or liquid phase, with sufficient sensitivity and selectivity, and in short time periods. In this review, we report the latest techniques for the detection of dioxins, furans and related compounds based on optical and spectroscopic methods, looking at future perspectives.